Javanese Women Under A Marriage Contract In Indonesia - Endah Kinasih, Sri; Koesbardiati, Toetik; Mas’udah, Siti (Opción, 2019)
This article investigates the process of a marriage contract and the factors affecting the women entering into a marriage contract. Employing the de- scriptive qualitative method, the research was conducted in Pasuruan, East Java and Bogor, West Java, Indonesia. The results of this study indicate that the marriage contract is conducted as sirri (unregistered) marriage in Islam where there is ijab qobul (marriage consent), consisting of a man, a woman, a witness and a penghulu (Muslim leader). A man from outside the village who wants a marriage contract has to undergo a more complicated process. The factors underlying the marriage are a lack of formal education, Muslim cler- ics (kyai) who allow marriage contracts under the pretext of legalizing sexual relations between men and women, and cultural factors where this form of marriage has been practiced for generations that is entrenched in the con- sciousness of the community.